Field Reporting on the Working of Village and Small Industries Scheme - Planning Commission (Planning Commission, 1970)
Programme Evaluation Organisation, at the instance of the Planning Commission, conducted a detailed study of development staff at the district and lower levels during the year 1968 in order to get the correct picture of the organisational structure of the district development staff. During this study wide disparities in organisational structures, overlapping functions in respect of issuing loans and grants and uncoordinated implementation of Industrial programme were noticed. It was, therefore, felt that a further probe of some of the important programmes could be undertaken, the working of village and small industries schemes being one of them. The present study was, therefore, taken up under the organisation programme of periodical field reporting other than its regular programme of intensive depth studies. The field work of the study was initiated in September,1969 and was completed in May,1970.
Programme Evaluation Organisation Planning Commission Government of India